Aspek-aspek Pedagogis dalam Amtsal al-Qur’an (kajian metodologis, motivasi, berfikir kritis dalam pembelajaran islam integratif) - Fatih, Muhammad (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2016)
As it is known that there are seven aspects related to pedagogical an educator, first, knowledge about the characteristics of learners, second, mastering learning theory and principles of learning that educates, third, developing a curriculum, fourth, learning activities that educate, fifth, development potential learners, sixth, communication with students, and the seventh, assessment and evaluation of learning outcomes. The use of methods amtsal help an educator in explaining the subject matter and bringing them closer to understanding and mastery of teaching materials. The problems of abstract packaged such that it becomes a concrete, tangible, and easily understood. Thus, the method amtsal assist in creating interesting communication between educators and learners. On the other hand, a method amtsal also assist educators in honing and developing the students' academic potential, and from here also the learning activities to be interesting, challenging and educational.